Engineering atomic metal active sites on polymeric carbon nitride for photocatalytic antibiotics treatment - Loh, Hong Yi (Nanyang Technological University, 2023)
Antibiotic resistance remains as one of the biggest threats to global health, food security, and development today, hence the demand for a novel water treatment process. This project aims to improve antibiotics treatment process via heterogeneous photocatalysis method by doping Iron on the Polymeric Carbon Nitride (PCN) catalyst, as well as investigate its photocatalytic mechanism. Currently, Advanced Oxidation Processes (AOP) based photocatalytic degradation face multiple efficiency challenges such as high surface recombination rates of excitons, low light absorption and short lifetime of photogenerated electrons. Herein, iron doped PCN (Fe-PCN) is synthesized using a one-pot method and its photocatalytic performance is tested using tetracycline (TC) as the organic pollutant. Despite retaining the same nanostructure as the pristine PCN, it is revealed that Fe-PCN shows enhanced photodegradation with a more extensive removal of Tetracycline TC. A typical AOP reaction pathway includes generation of highly Reactive Oxygen Species (ROS) such as hydroxyl radicals (•OH) and superoxide anion (•O2-) to break down organic pollutants to non-toxic intermediates. Remarkably, Fe-PCN demonstrated no ROS production to achieve efficient TC decomposition. Thus, a possible reaction mechanism responsible for such a phenomenon was proposed.